0
$\begingroup$

I am pretty sure it's duplicate but on the other hand it's hard to find by a title.

I am having hard time showing that every matrix in $SU(2)$ is of the form $\begin{pmatrix}z & -\overline w \\ w & \overline z\end{pmatrix}$ for some $z, w \in \mathbb{C}$ such that $|z|^2 + |w|^2 =1$. In most of the sources (including answers here) it is stated as something well-known. It is indeed well-known but I have never seen a proof and couldn't come up with one.

$\endgroup$
  • $\begingroup$ Seems like you also need $|z|^2+|w|^2=1$, right? For instance $\begin{bmatrix}2&0\\0&2\end{bmatrix}$ isn't in $\mathrm{SU}(2)$. $\endgroup$ – carmichael561 May 19 at 20:04
  • 1
    $\begingroup$ Hint: Do you know the explicit form of the inverse of $\begin{pmatrix}a&b\\c&d\end{pmatrix}$? $\endgroup$ – Toffomat May 19 at 20:06
2
$\begingroup$

Let $\begin{bmatrix}x_1 & x_2\\x_3 & x_4\end{bmatrix}\in SU(2),$ then $x_1\cdot x_4-x_3\cdot x_2=1$ because determinant is $1$(this you did not mention) and $$\begin{bmatrix}\overline{x_1} & \overline{x_3}\\\overline{x_2} & \overline{x_4}\end{bmatrix}=\begin{bmatrix}x_4 & -x_2\\-x_3 & x_1\end{bmatrix}$$ so $x_1=\overline{x_4}$ and $\overline{x_2}=-x_3.$ Notice that the other $2$ equations are just manipulations of these two. Check that left hand side is the inverse of the matrix and the left hand side is the adjoint.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

Note that $$\text{SU}(2):={\{A\in M(2,\mathbb{C}): \langle Ax,Ay\rangle,\; \forall x,y\in\mathbb{C}^2,\;\text{det}(A)=1}\}$$ where $\langle x,y\rangle:=x_1\bar{y_1}+x_2\bar{y_2}.$ Then $$\text{SU}(2):={\{A\in M(2,\mathbb{C}): AA^*=A^*A=I_2,\;\text{det}(A)=1}\}$$ where $A^*=\overline{(A^{t})}.$

So for all $A=\begin{pmatrix}a & b \\ c & d\end{pmatrix}\in\text{SU}(2)$ It is true that $A^{-1}=A^{*}\;\text{and}\;\text{det}(A)=1$:

$A^{-1}=\begin{pmatrix}d & -b \\ -c & a\end{pmatrix}$ and $A^{*}=\begin{pmatrix}\overline{a} & \overline{c} \\ \overline{b} & \overline{d}\end{pmatrix}$ hence $A^{-1}=A^*$ implies that $$d=\overline{a}\;\text{and}\; b=-\overline{c}.$$ Then $A=\begin{pmatrix}a & -\overline{c} \\ c & \overline{a}\end{pmatrix}.$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.